2021
DOI: 10.1155/2021/8858006
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activities of Ginsenosides, the Main Active Components of Ginseng

Abstract: Cancer incidence rate has been increasing drastically in recent years. One of the many cancer treatment methods is chemotherapy. Traditional medicine, in the form of complementary and alternative therapy, is actively used to treat cancer, and many herbs and active ingredients of such therapies are being intensely studied to integrate them into modern medicine. Ginseng is traditionally used as a nourishing tonic and for treating various diseases in Asian countries. The therapeutic potential of ginseng in modern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 133 publications
0
27
0
Order By: Relevance
“…Z-Ligustilide extracted from Angelica sinensis can inhibit the growth of mouse prostate cancer cells by demethylation of the promoter of the tumor suppressor gene NFE2 Like BZIP Transcription Factor 2 (NrF2) ( Su et al, 2013 ). Ginseng (Ren Shen in Chinese), which is a rhizome from the Araliaceae and has multiple anti-tumor effects ( Hong et al, 2021 ), should be one of the most studied TCMs. Ginsenoside Rg3 was one of main ingredients found to have a global hypomethylation effect in human hepatoma cell line HepG2 ( Teng et al, 2017 ).…”
Section: The Effect Of Traditional Chinese Medicine On the Regulation...mentioning
confidence: 99%
“…Z-Ligustilide extracted from Angelica sinensis can inhibit the growth of mouse prostate cancer cells by demethylation of the promoter of the tumor suppressor gene NFE2 Like BZIP Transcription Factor 2 (NrF2) ( Su et al, 2013 ). Ginseng (Ren Shen in Chinese), which is a rhizome from the Araliaceae and has multiple anti-tumor effects ( Hong et al, 2021 ), should be one of the most studied TCMs. Ginsenoside Rg3 was one of main ingredients found to have a global hypomethylation effect in human hepatoma cell line HepG2 ( Teng et al, 2017 ).…”
Section: The Effect Of Traditional Chinese Medicine On the Regulation...mentioning
confidence: 99%
“…Since ancient times, ginseng has been found to possess multiple pharmacological effects and has been used to treat various diseases, such as inflammation, cancers, metabolic syndromes, and autoimmune diseases. The anti-cancer effect of ginseng has attracted increasing interest and attention in the fields of various cancers, including ovarian cancer, CRC, breast cancer, lung cancer, prostate cancer, and liver cancer ( 31 34 ). Many in vitro and in vivo studies have demonstrated that ginseng or its extracts could significantly decrease the incidence of CRC and inhibit tumor growth ( 35 ).…”
Section: Ginsengmentioning
confidence: 99%
“…Various ginsenosides have demonstrated anticancer properties in vitro and in vivo following the inhibition of cell cycle, angiogenesis, and the induction of apoptosis in different types of malignancies [ 328 , 330 ].…”
Section: Plants From Different Continents Used In Ethnomedicine For T...mentioning
confidence: 99%